Extension on Early Detection of Tuberculosis Suspects to Health Cadres in Buntalan Village, Central Klaten Community Health Center - Sutaryono Sutaryono; Rezyana Budi Syahputri (WASATHON Jurnal Pengabdian Masyarakat, 2024)
The discovery of suspected Tuberculosis during the COVID-19 pandemic has decreased, in the last 3 years Klaten Regency has also had an impact in the discovery of suspected TB. This hinders the achievement of TB elimination by 2030. Therefore, participation is needed from all elements, including government, private sector, educational institutions and the community. Community service activities in the form of outreach on early detection of tuberculosis with TB friends at Klaten Regency health center cadres are a form of the Tridharma of Universitas Muhammadiyah Klaten. Community service activities include observation and coordination, formulation of cooperation, socialization of programs to health cadres, counseling to health cadres. Counseling will be held on Saturday 23 September 2023 from 13.00 to 15.00 WIB. The participants in the counseling were 22 health cadres, 3 students with as resource from Universitas Muhammadiyah Klaten and Dinas Kesehatan Kabupaten Klaten. The results of community service activities can provide education on early detection of tuberculosis with TB friends at Klaten Regency health center cadres. This outreach is able to increase the knowledge of health cadre participants about Tuberculosis and provide early detection in the community. As a follow-up, cadre assistance is needed to be able to find new cases of tuberculosis in their environment